Faptul magic şi faptul mistic. Prima întâlnire a lui Eliade cu opera lui Evola - Liviu Bordaș (Revista de Istorie și Teorie Literară)
This article is the first in a series to offer a historical reconstruction of Mircea Eliade’s relationship with the main representatives and ideas of the so-called “Traditionalist” current (René Guénon, Julius Evola, and Ananda K. Coomaraswamy). Eliade first comes across the works of the Traditionalists between 1926 and 1928. I examine the motives that might have brought about his interest for their works, his relation to their ideas, and the immediate consequences of this intellectual encounter during his first months in India. My claim is that Guénon and Coomaraswamy have a rather limited impact on his intellectual formation at this early stage. Evola’s work (more precisely his less known articles from the reviews „Bilychnis” and „Ur”), on the other hand, seems to have captivated the imagination of young Eliade. However, the positions of Evola with which he found himself in agreement (his “magic idealism”) were gained independently, through his own “spiritual itinerary”, as well as through his earlier acquaintance with the seminal works of Macchioro, Frazer, and Otto. But Eliade also disagrees with Evola on several counts. My argument is that Evola acts as a catalyst, and that Eliade develops many of his theoretical positions largely on his own. We can not speak, at least at this stage, of an influence, but rather of convergence. Other authors also played a similar catalytic role in shaping Eliade’s ideas about magic and mystic, in particular Nae Ionescu (his professor at the University of Bucharest), and the indologists John Woodroffe and Jakob Wilhelm Hauer. Subsequent articles will trace the course of Eliade’s involvement with the works of the Traditionalists during his Indian period (1929–1931), the period after his return to Romania (1932–1940), and during the World War II (1940–1945).